2021
DOI: 10.1016/j.clinimag.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Computed Tomography Angiography and Venography in Evaluation of Hemorrhagic and Thrombotic lesions in Hospitalized COVID-19 patients

Abstract: Purpose To report imaging findings at computed tomography angiography (CTA) and venography (CTV) of the abdomen and pelvis in evaluation of hemorrhagic and thrombotic lesions in hospitalized patients with COVID-19. Methods In this retrospective observational study, patients admitted to a single tertiary care center from April 1 to July 20, 2020, who tested positive for SARS-CoV-2 and developed acute abdominal pain or decreasing hemoglobin levels over the course of hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 33 publications
(37 reference statements)
2
19
1
Order By: Relevance
“…Similarly, Abdelmohsen reports that in 27 of 40 patients (67.5%), a CT scan revealed acute vascular pathologies. Therefore, the authors highlight the importance of abdominal CT imaging in COVID-19 patients [ 7 ]. Considering the high mortality rate in case of delayed surgery, the therapeutic algorithm for COVID-19 patients should include a rapid indication for surgery, if there are clinical or radiological signs of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Abdelmohsen reports that in 27 of 40 patients (67.5%), a CT scan revealed acute vascular pathologies. Therefore, the authors highlight the importance of abdominal CT imaging in COVID-19 patients [ 7 ]. Considering the high mortality rate in case of delayed surgery, the therapeutic algorithm for COVID-19 patients should include a rapid indication for surgery, if there are clinical or radiological signs of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In our study 13 patients had abdominal thrombosis, 5 of them required extracorporeal membrane oxygenation (ECMO). On various imaging methods, the presence of a filling defect within a vessel, with or without occlusion, is the characteristic finding of venous thrombosis [3,10]. CT angiography/venography helps for adequate evaluation of thrombus extension into central veins.…”
Section: Discussionmentioning
confidence: 99%
“…This study disagreed with the previous research by Vadvala et al [ 20 ] which reported that the bleeding complications with or without contrast extravasation were most commonly seen in 71% of included patients, while thromboembolic and ischemic complications were seen only in 17.8% of patients. Other worldwide researchers also disagreed with this, including Shah et al [ 21 ], Lodigiani et al [ 22 ], Lee et al [ 23 ], O'Shea et al [ 24 ], Abdelmohsen et al [ 25 ].…”
Section: Discussionmentioning
confidence: 99%